The Lysostaphin Endopeptidase Resistance Gene (epr) Specifies Modification of Peptidoglycan Cross Bridges in Staphylococcus simulans and Staphylococcus aureus - DeHart, H. P. (1995)
Volume 61, no. 4, p. 1478, Table 2, column 4: The diameters (in milliliters) of the zones of inhibition for 5-(mu)g methicillin disks given (from top to bottom), "116," "72," "107," and "32," should read "33.5," "22.6," "34.2," and "21.0," respectively.